Synthesis of Fluorescence Carbon Nanoparticles from Ascorbic Acid - Sri Sugiarti; Noviyan Darmawan (Universitas Gadjah Mada, 2015)
Carbon nanoparticles (C-dot) are materials that belong to a class of 0-dimensional nanoparticles with a photoluminescence property. C-dot can be synthesized from a variety of organic acids through bottom-up synthetic methods or from other source of inorganic carbons through top-down synthetic methods. Herein, we report a simple and fast synthesis method for the formation of C-dot from ascorbic acid using microwave heating technique. The success of this synthesis was shown by visual analysis, UV-Vis spectroscopy, fluorescence spectroscopy, and transmission electron microscopy (TEM). Visual analysis showed an increased in fluorescence intensity with the addition of urea as a passivation agent. The maximum fluorescence emission of the C-dot was a blue green color at wavelength 500 nm, after the C-dot was excited at a wavelength of 400 nm. The TEM analysis showed that the synthesized C-dot had an average size of 18 nm. We also conducted a preliminary study on the synthesized C-dot as a heavy ion metal sensor and found selective identification of Cr metal.